2013
DOI: 10.1590/s0001-37652013005000008
|View full text |Cite
|
Sign up to set email alerts
|

Construction of yellow fever virus subgenomic replicons by yeast-based homologous recombination cloning technique

Abstract: RNA replicon derived from Flavivirus genome is a valuable tool for studying viral replication independent of virion assembly and maturation, besides being a great potencial for heterologous gene expression. In this study we described the construction of subgenomic replicons of yellow fever virus by yeast-based homologous recombination technique. The plasmid containing the yellow fever 17D strain replicon (pBSCrepYFV-17D), previously characterized, was handled to heterologous expression of the green fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…This interaction occurs in a region (the interaction domain of RNApol domain) that is conserved in several flaviviruses and that is, therefore, likely to be relevant to the genus. Although eIF3L overexpression and plaque reduction assays (using an YFV replicon [13]) demonstrated a slight (if any) inhibition of YFV replication, we were able to demonstrate that eIF3L overexpression facilitates translation, with potential implications in viral replication.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…This interaction occurs in a region (the interaction domain of RNApol domain) that is conserved in several flaviviruses and that is, therefore, likely to be relevant to the genus. Although eIF3L overexpression and plaque reduction assays (using an YFV replicon [13]) demonstrated a slight (if any) inhibition of YFV replication, we were able to demonstrate that eIF3L overexpression facilitates translation, with potential implications in viral replication.…”
Section: Introductionmentioning
confidence: 65%
“…For overexpression, BHK-21-Rep-YFV17D LucNeoIres cells, a stable bicistronic dual-reporter YFV replicon cell line expressing the neomycin phosphotransferase resistance gene and the reporter gene firefly luciferase [13], were used. The cells were transfected with the pCDNAFlag-eIF3L plasmid or an empty vector.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we report the first reverse genetics system for IBDV constructed from homologous recombination in yeast. This method has been described in the literature for the genetic manipulation of other viruses, such as Yellow Fever ( Queiroz et al , 2013 ) and HIV-1 ( Marozsan and Arts, 2003 ) and it has shown to be efficient and easier to perform compared to the use of restriction enzymes and in vitro ligation.…”
Section: Discussionmentioning
confidence: 99%
“…1c and Table 2). Self-replicating subgenomic replicons are genetically engineered viral RNA molecules that are shorter than full-length viral genomes and are capable of replication but incapable of producing virions [22,29,62,70]. However, they can be packaged into viral particles if viral coat proteins are provided [62].…”
Section: General Principles Of Live Cell Reporter Systemsmentioning
confidence: 99%
“…Self-replicating subgenomic replicons are genetically engineered viral RNA molecules that are shorter than full-length viral genomes and are capable of replication but incapable of producing virions [22,29,62,70]. However, they can be packaged into viral particles if viral coat proteins are provided [62]. For Flaviviridae viruses, such as CSFV, two self-replicating RNAs (replicons) were produced by replacing the coding region for C to E2 of CSFV with the Rluc sequence or the coding region for C to E1 with the Rluc-2A sequence [63].…”
Section: General Principles Of Live Cell Reporter Systemsmentioning
confidence: 99%